2014
DOI: 10.2147/oajc.s56349
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and patient acceptability of the etonogestrel and ethinyl estradiol vaginal ring

Abstract: Abstract:The contraceptive vaginal ring (CVR) is a combined hormonal contraceptive method, containing ethinyl estradiol and etonogestrel, that works by inhibiting ovulation. It differs from combined oral contraceptives (COCs) in the route of administration, which is vaginal, and the frequency of administration, which is monthly. The efficacy of the CVR is similar to that of COCs but compliance appears to be better in typical users. The CVR enables appropriate control of the menstrual cycle, with a similar side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Unlike Vieta et al (2011) but in line with other reports, we did not find a higher placebo response in the US studies (Watsky et al, 2009). Geographic differences in drug efficacy have been reported for other health issues/conditions, including cardiovascular disease (Blair et al, 2008;Mentz et al, 2012;Stough et al, 2007) and contraception in contraceptive trials (Grubb et al, 2008;Lete et al, 2014). Despite the efforts of Blair et al (2008) in the EVEREST study to select a fairly homogenous population of patients with heart failure, important differences in etiology, severity, management, and outcomes were found (Blair et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Vieta et al (2011) but in line with other reports, we did not find a higher placebo response in the US studies (Watsky et al, 2009). Geographic differences in drug efficacy have been reported for other health issues/conditions, including cardiovascular disease (Blair et al, 2008;Mentz et al, 2012;Stough et al, 2007) and contraception in contraceptive trials (Grubb et al, 2008;Lete et al, 2014). Despite the efforts of Blair et al (2008) in the EVEREST study to select a fairly homogenous population of patients with heart failure, important differences in etiology, severity, management, and outcomes were found (Blair et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A review by Mentz et al (2012) also found differences in outcome and baseline characteristics of patients with different types of cardiovascular disorders (heart failure, acute coronary syndromes, hypertension, and atrial fibrillation) across geographic regions (Stough et al, 2007). Similarly, efficacy of contraceptives frequently showed lower efficacy in clinical trials conducted in US patients compared to trials conducted in Europe (Grubb et al, 2008; Lete et al, 2014), an issue that was addressed by the FDA (FDA, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, ring-usage is also associated with increased incidence and severity of local side e ects such as leukorrhea and vaginitis. (42) Conclusion/Future Directions e development of novel non-hormonal birth-control methods is imperative as hormonal contraceptives have been associated with an increased risk of depression (8,38) and are not suitable for women with certain pre-existing conditions. ( 44) LIF modulation could potentially be e ective for this purpose.…”
Section: Hormonal Contraceptivesmentioning
confidence: 99%
“…To conclude, present research suggests that vaginally administered PEG-LA could be as e ective as hormonal contraceptives in terms of preventing pregnancy in women. (7,9,21) While systemic LIF-modulation has been shown to be associated with altered bone density, vaginal administration of PEGLA seems to mitigate this risk without enhancing local side e ects, which was the case when hormonal contraceptives were administered vaginally (9,42) erefore, in terms of mitigating negative side e ects and thereby increasing clinical desirability, vaginally administered LIF-modulating contraceptives could be preferable to hormonal contraceptives. [1] Decidualization is the process by which stromal cells di erentiate, resulting in the formation of a "decidua", which provides the blastocyst with nutrients until the functional placenta is formed, while simultaneously restraining trophoblast-uterine invasion.…”
Section: Hormonal Contraceptivesmentioning
confidence: 99%